Dual class firms: Capitalization, ownership structure and recapitalization back into single class - Amoako-Adu, Ben; Smith, Brian F. (Journal of Banking & Finance, 2001)
This paper analyses changes in capitalization and control of dual class firms before and after IPO. The results indicate that the combination of a large controlling shareholder with family interests, rather than concentrated ownership per se, leads to dual class capitalization. During the first 15 years post-IPO, voting leverage continuously increases as the dual class firms issue more restricted than superior voting shares. However, control changes are equally frequent for dual and single class firms suggesting that dual class capitalization is not used to unduly entrench management. We document disputes between restricted and superior voting shareholders to illustrate the potential corporate governance problems which are associated with dual class capitalization. As a result of these disputes, investor interest in dual class equity has decreased and there is a recent trend toward reclassification back into single class equity.